Bilateral lung lesions with breast metastasis: a case report - Bakar, Nor Salmah; Harun, Norra; Ng, Teck Han (College of Pathologists, Academy of Medicine Malaysia, 2010)
Background: Development of metastasis to the breast from lung cancer is very rare. Methods: We present a 22-year-old lady who had multifocal and bilateral lung lesions, metastasize to the left breast. Physical examination, CT scan and cytologic and histology study on breast biopsy were performed. Results: Patient was a 22-year-old lady presented with history of cough for 4 months prior to the hospital admission. The cough was productive with greenish sputum on and off. Occasionally, she also noted small amount of blood in her sputum. Other associated symptoms include hoarseness of voice, fatigue, loss of appetite and loss of weight. She was anaemic and found to have cervical lymphadenopathy, vocal cord palsy and right facial nerve palsy. Computed Tomography Scan of neck and thorax revealed multiple neck and mediastinal lymph nodes and multiple lung nodules which were seen in both lung fi elds. The left breast lump was identifi ed on admission. She underwent series of cytologic and histologic examination of the neck swellings and the left breast lump. Both lesions showed an adenocarcinoma; with the left breast lesion appeared rather poorly differentiated but exhibited focal positivity for mucin stain. Both neck and left breast lesions were positive for Cytokeratin 7(CK7), and TTF1, while negative for CK20, Estrogen receptor (ER), Progestrone receptor (PR) and thyroglobulin. Conclusion: Thorough morphologic assessment together with support from panels of immunohistochemical stains and special stain are able to indicate the possible primary source of malignancy. It is important to distinguish a primary breast cancer from a metastasis to the breast, as the therapeutic planning and the outcome between them are different.